PENGARUH PERILAKU SUPERVISI AKADEMIK, PENELITIAN PENGEMBANGAN DAN EVALUASI PENDIDIKAN PENGAWAS SEKOLAH PADA KINERJA GURU STUDI DI SMK MA'ARIF KABUPATEN KULON PROGO - , Sumiyati; , Gugup Kismono, MBA., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to 1) analyze the influence of the school superintendent Academic Supervision on teacher performance, 2). analyze the effect of development on the school superintendent teacher performance, and 3). analyzed the effect of Educational Evaluation school superintendent on teacher performance. The population in this study was the teacher of SMK Maâarif in KulonProgo which consists of 270 teachers spread over 5 districts. Sampling used proportionate stratified random sampling. Study sample: 60% of the population or as many as 162 respondents. Methods of data collection used questionnaires. Quantitative descriptive data analysis and regression analysis. Based on data analysis and the discussion concluded that: 1). There is a positive influence on the school superintendent Academic Supervision on teacher performance, but not significantly. It is shown from the results of the regression test has a coefficient of 0.049 with a significance level of 0.720. It is also possible for some teachers who guided the school superintendent is not the same field of study, so it does not support its performance. 2). No positive effect on the school superintendent Development Research on teacher performance, even a negative effect. It is shown from the results of the regression test that has a coefficient of - 0.090, and 0.420 significance level. Probably caused by supervisorâs lack of oversight in guiding teacher on research and development, so it does not support its performance. 3). There is a positive influence on the school superintendent Evaluation Education on teacher performance. It is shown from the results of the regression test to get a coefficient of 0.421 with a significance level of 0.000. This is because the evaluation of educational supervision is directly related to how to conduct evaluations to their students, thus supporting teacher performance.